ENDANGERING TO SAFETY AND ENDANGERING TO SECURITY IN THE CRIMINAL LAW OF THE REPUBLIC OF SRPSKA - SIMILARITIES AND DIFFERENCES - Sladić, Ljubana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
In the positive legal system of the Republic of Srpska, endangering to safety and endangering to security are regulated as two different criminal offenses, in such a way that endangering safety is prescribed as a criminal offense against the freedoms and rights of citizens, while endangering to security (threat of an attack on life, body or property) is prescribed as misdemeanor against public order and peace. The paper will analyze both of these criminal acts, with the aim of highlighting the similarities and differences between them and possibly, after that analysis, determining whether there is still a need for both acts, prescribed in this way, to exist in positive legal system. The author proposes de lege ferenda to correct the legal description and name of the misdemeanor endangering security by threatening to attack life, body or property in such a way that this misdemeanor only bears the name of threat and that the legal description expressly states that the place of execution is a public place or prescribe as consequence a violation of public order and peace or to decriminalize this misdemeanor because everything that this offense currently provides protection for is already sufficiently and adequately protected by the criminal offense of endangering safety.